Research note: Extraction, purification, physicochemical, and biochemical properties of pepsin isolated from geese forestomachs fed under intensive and extensive conditions - Beyazgul, Pelin; Tonbak, Fadime; Ozmen, Gorkem Kirmizikaya; Baykalird, Yasin; Simsek, Ulku Gulcihan; Arslan, Ali; Yimaz, Okkes (Elsevier, 2026)
This Research Note reports the isolation and basic characterization of pepsin obtained from the forestomach of geese raised under intensive and extensive rearing systems. Crude and purified enzyme fractions were obtained using gel filtration chromatography, and their milk-clotting and proteolytic activities were evaluated. Pepsin activity differed between rearing systems as well as between crude and purified fractions. The molecular weight of goose pepsin was approximately 35 kDa as determined by SDS-PAGE. While crude pepsin protein concentrations varied significantly between intensive and extensive systems, purified enzyme concentrations were comparable. Microbiological analyses indicated that all crude and purified pepsin samples were below detectable limits for the tested microorganisms (<1.0 log CFU/mL). These findings provide preliminary evidence that rearing conditions may influence certain functional properties of goose pepsin, while purification yields a microbiologically safe enzyme preparation.
Keywords: Gel filtration chromatography; Geese forestomach; Pepsin; SDS-PAGE; Intensive-extensive raising